Inclusiveness Index - Othering and Belonging Institute (Othering and Belonging Institute, 2023)
The Othering and Belonging Institute’s “Inclusiveness Index” is a holistic gauge of the degree of inclusivity experienced by marginalized groups across the globe. The 2022 index ranks states and countries in absolute and relative terms using a variety of indicators.
Keywords: 2023-10 October